Prevalence and associated factors of structural congenital anomalies in resource limited setting, 2023: a systematic review and meta-analysis - Geda, Yohannes Fikadu; Lamiso, Yirgalem Yosef; Berhe, Tamirat Melis; Chibsa, Samuel Ejeta; Sahle, Tadesse; Assefa, Kenzudin; Mohammed, Seid Jemal; Abeje, Seblework; Gesese, Molalegn Mesele (Frontiers in Pediatrics, 2023)
Background Several studies have been conducted on structural congenital anomalies (CA). However, there is a paucity of studies that provide a comprehensive review of structural anomalies. We aimed to verify the available research articles to pool the possible risk factors of structural CA in resource-limited settings. Setting The research articles were genuinely searched using PubMed, Scopus, Cochrane Library, Web of Science, free Google database search engines, Google Scholar, and ScienceDirect databases. Published studies were searched and screened for inclusion in the final analysis, and studies without sound methodologies and review and meta-analysis were not included in the analysis. Participants This review analyzed data from 95,755 women who gave birth as reported by primary studies. Ten articles were included in this systematic review and meta-analysis. The articles that had incomplete information and case reports were excluded from the study. Results The overall pooled effect estimate (EI) of structural CA was 5.50 (4.88–6.12) per 100 births. In this systematic review and meta-analysis, maternal illness EI with odds ratio (OR) = 4.93 (95% CI: 1.02–8.85), unidentified drug use with OR = 2.83 (95% CI: 1.19–4.46), birth weight with OR = 4.20 (95% CI: 2.12–6.28), chewing chat with OR = 3.73 (95% CI: 1.20–6.30), chemical exposure with OR = 4.27 (95% CI: 1.19–8.44), and taking folic acid tablet during pregnancy with OR = 6.01 (95% CI: 2.87–14.89) were statistically significant in this meta-regression. Conclusions The overall pooled effect estimate of structural CA in a resource-limited setting was high compared to that in countries with better resources. Maternal illness, unidentified drug use, birth weight, chewing chat, chemical exposure, and never using folic acid were found to be statistically significant variables in the meta-regression. Preconception care and adequate intake of folic acid before and during early pregnancy should be advised. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/, identifier CRD42022384838.